Chess tournament management system (pairing module) - Yeow, Chee You (2005)
Chess is one of the student's favourite sports in KUKTEM. All Chess tournaments in KUKTEM are organized by chess club. Unfortunately, tournaments cannot run smoothly due to problems that occurred during the tournaments' management process.Lateness of pairing and unfair colour allocation was among the problems that should be overcome by Chess Club generally.Involvement of too many players in a particular tournament causes lateness. The organizer has to waste a lot of time in chess pairing. Besides that, problems of unfair colour allocation lead to argument among players. All players prefer white colour rather than black colour because they got better chance to win if they are white side. Furthermore,mistake always occurred when tournament comes to heavy task like chess pairing and colour allocation.This cause players complaint about the unfair treatments in the tournament. So for that, in order to overcome the problem, Chess Pairing module needs to be developed.The development of chçss pairing module of Chess Tournament Management System is suggested for handling the player pairing and colour allocation in every match.A Software Development Life Cycle (SDLC) is use as a method in the development of this system.Chess Pairing module will use Gale Shapley method as a based idea to develop an algorithm to do the entire pairing and colour allocation task.